The Fourth Industrial Revolution and the New Path of Law - Simonyan, Taron (Bulletin of Yerevan University C: Jurisprudence, 2023)
The contemporary accelerating changes in technology lead to drastictransformations in economy, social and political structures, as well as legal practice andthe very essence of law. The present research is a try to bring to the light the evolutionof industrial revolutions and realize the transformations and developments of law andlegal practice throughout the First, Second, Third and Fourth Industrial Revolutions.Taking into account the consequences of the previous industrial revolutions andthe ongoing nature of the Fourth Industrial Revolution, the research defines somegeneral developments / paths in the law, especially the transformations in legal practice(Practical Perspective); transformations in teaching law (Educational Perspective) andtransformation in the essence and perception of law itself (Theoretical Perspective).Based on the research two possible social structures, with economic, political andlegal order, have been proposed: negative and positive.
Keywords: industrial revolutions; accelerating changes; artificial intelligence; LegalTech; transformation in legal practice; transformation in teaching law; transformation in perception of law